Human Resource Management Practices and Job Performance Under Investigation: Mediating Role of Job Satisfaction and Employee Value Proposition - Kurniawan, Harisnu; Desiana, Putri Mega (Universitas Airlangga, 2024)
Objective: This study investigates the influence of human resource management practices on job performance by mediating job satisfaction and employee value proposition among state-owned enterprise company employees. Design/Methods/Approach: This study was analyzed using an explanatory research approach with quantitative data collected through structured questionnaires involving 396 employees. Path Analysis was employed to investigate the research data using the Structural Equation Model and LISREL as statistical data processing tools. Findings: The results show that human resource management practices do not directly, positively, and significantly impact job performance in the company. However, the findings indicate a significant favorable influence of Human Resource Management Practices on Job Performance by mediating Job Satisfaction and Employee Value Proposition. Originality/Value: The existing literature highlights the unclear relationship between Human Resource Management Practices and Job Performance, often resembling a 'black box,' emphasizing the necessity to identify mediating variables operating through unexplained mechanisms. This study contributes to the existing literature by investigating the mediation role of employee value proposition alongside job satisfaction and explaining the relationship between human resource management practices and job performance in a state-owned enterprise. Practical/Policy implication: The state-owned enterprise company is advised to improve job satisfaction and perceived employee value proposition to increase job performance. Specifically, the state-owned enterprise company should improve its human resource management practices by providing better job stability and competitive salaries and incentives.